2013
DOI: 10.1007/8904_2013_260
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Folic Acid and High Plasma Folate in Children and Adults with Phenylketonuria

Abstract: Children with PKU are at a particular risk of receiving folic acid high above RDI and many children with PKU receive doses above the UL. Many PKU patients have a very high level of plasma folate related to a very high content of folic acid in many of their protein substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
4
11
0
1
Order By: Relevance
“…Our findings are confirmed by the study by Stolen et al [38] reporting similar results. As there is discussion on the safety of high concentrations [38,39,] it deserves due consideration to lower folic acid amounts in AAM. For example, high levels of folic acid have been associated with interference in DNA and histone methylation, decreased natural killer cell toxicity, an increased risk of cognitive impairment in the elderly and facilitating progression of preneoplastic cells and subclinical cancers.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings are confirmed by the study by Stolen et al [38] reporting similar results. As there is discussion on the safety of high concentrations [38,39,] it deserves due consideration to lower folic acid amounts in AAM. For example, high levels of folic acid have been associated with interference in DNA and histone methylation, decreased natural killer cell toxicity, an increased risk of cognitive impairment in the elderly and facilitating progression of preneoplastic cells and subclinical cancers.…”
Section: Discussionsupporting
confidence: 83%
“…Because all patients off diet showed serum concentrations within normal range, elevated serum concentrations appear to be due to fortified AAM [37]. Our findings are confirmed by the study by Stolen et al [38] reporting similar results. As there is discussion on the safety of high concentrations [38,39,] it deserves due consideration to lower folic acid amounts in AAM.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, some studies have demonstrated high folate levels in patients associated with the high folate content of Phe-free L-amino acid supplements with added vitamins and minerals [ 118 , 127 , 130 ]. The long- term consequences of folate overload in PKU have not been assessed.…”
Section: Treatment Goals and Follow-upmentioning
confidence: 99%
“…According to some authors, PKU and HPA patients may receive excessive amounts of vitamin B 12 and folate (40)(41)(42). The risks of possible side effects from such a status, and particularly in relation to tumor growth are often discussed in literature.…”
Section: Discussionmentioning
confidence: 98%